Thermally stable nickel-rich cathode

By constructing a thermally stable nanoparticle layer on the surface of nickel-rich active material particles, the thermal stability problem of nickel-rich cathode under high temperature conditions is solved, and higher thermal stability and battery pack performance is achieved, while reducing manufacturing complexity.

CN119650803APending Publication Date: 2025-03-18GM GLOBAL TECHNOLOGY OPERATIONS LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311204732.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-18
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The nickel-rich cathode in the Hyundai Automobile High Voltage Battery Pack has thermal stability problems under high temperature conditions, resulting in degradation of the battery pack and shortening the cycle life.

Method used

By constructing a nanoscale thermal suppression layer on the surface of nickel-rich active material particles, the slurry formed is used to make a thermally stable nickel-rich cathode using a combination of heat-stable olivine, spinel and manganese-nickel dioxide nanoparticles.

Benefits of technology

Improves thermal stability of nickel-rich cathodes, reduces energy density trade-offs, enhances battery pack performance and cycle life, while simplifying the manufacturing process, suitable for integration of existing plant facilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650803A_ABST
    Figure CN119650803A_ABST
Patent Text Reader

Abstract

Aspects of the present disclosure include systems and methods for making thermally stable nickel-rich cathodes. An exemplary method may include providing an active material including a plurality of active material particles. The plurality of active material particles includes nickel. A nanoparticle slurry additive having a plurality of nanoparticles is provided. The plurality of nanoparticles includes one or more of a thermally stable olivine-type material, a thermally stable spinel-type material, and a thermally stable manganese-nickel dioxide-type material. The method includes forming a slurry by mixing an active material and a nanoparticle slurry additive. A plurality of nanoparticles are formed on a surface of the plurality of active material particles and a thermal inhibition layer in direct contact therewith. A self-supporting electrode film is formed by rolling the slurry, and the self-supporting electrode film is laminated onto a current collector to define a thermally stable nickel-rich cathode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The subject disclosure relates to battery cell technology and, in particular, to thermally stable nickel-rich cathodes. Background Art

[0002] The subject disclosure relates to battery cell technology and, in particular, to thermally stable nickel-rich cathodes.

[0003] High voltage electrical systems are increasingly used to power onboard functions of mobile and stationary systems. For example, in motor vehicles, the need to improve fuel economy and reduce emissions has led to the development of advanced electric vehicles (EVs). EVs rely on a rechargeable energy storage system (RESS), which typically includes one or more high voltage battery packs, and an electric drivetrain that transfers power from the battery packs to the wheels. The battery pack may include any number of interconnected battery modules depending on the power requirements of a given application. Each battery module includes a group of conductively coupled electrochemical cells. The battery pack is configured to provide a direct current (DC) output voltage at a level suitable for powering a coupled electrical and / or mechanical load (e.g., an electric motor).

[0004] The cathode (positive electrode) in a battery pack is one of the key components responsible for the electrochemical reactions that occur during the charging and discharging process. Modern automotive high-voltage battery packs benefit from high energy density cathodes to improve overall performance and range. For example, nickel-rich cathodes have a higher theoretical specific capacity compared to many other materials (such as iron-based and manganese-based cathodes). This means that nickel-rich cathodes can store more energy per unit mass, resulting in a battery pack with a higher energy density. Summary of the invention

[0005] In an exemplary embodiment, a vehicle includes an electric motor and a battery pack electrically coupled to the electric motor. The battery pack includes an electrochemical cell. The electrochemical cell includes a cathode, an anode, and an electrolyte system between the cathode and the anode. The cathode includes an active material including a plurality of active material particles. The plurality of active material particles include nickel. The cathode also includes a thermal inhibition layer formed on a surface of each of the plurality of active material particles and in direct contact with the active material particles. The thermal inhibition layer includes a plurality of nanoparticles. The plurality of nanoparticles include one or more of a thermally stable olivine-type material, a thermally stable spinel-type material, and a thermally stable manganese-nickel dioxide-type material.

[0006]

[0013] In addition to one or more features described herein, in some embodiments, the plurality of nanoparticles includes a combination of two or more of a thermally stable olivine-type material, a thermally stable spinel-type material, and a thermally stable manganese-nickel dioxide-type material.

[0007] In some embodiments, the thermally stable olivine-type material includes one or more of lithium vanadium phosphate, lithium iron manganese phosphate, cobalt phosphate, and lithium titanium phosphate.

[0008] In some embodiments, the thermally stable spinel-type material includes one or more of lithium manganese oxide and lithium manganese nickel oxide.

[0009] In some embodiments, the thermally stable manganese-nickel dioxide type material includes one or more of lithium manganese dioxide and lithium manganese nickel dioxide.

[0010] In some embodiments, the mass ratio of the plurality of nanoparticles to active material in the cathode is less than 30%.

[0011] In some embodiments, the surface coverage of the active material by the plurality of nanoparticles is between 10% and 95%.

[0012] In another exemplary embodiment, the electrochemical cell may include a cathode, an anode, and an electrolyte system between the cathode and the anode. The cathode includes an active material including a plurality of active material particles. The plurality of active material particles include nickel. The cathode also includes a thermal inhibition layer formed on the surface of each of the plurality of active material particles and in direct contact with the active material particles. The thermal inhibition layer includes a plurality of nanoparticles. The plurality of nanoparticles include one or more of a thermally stable olivine-type material, a thermally stable spinel-type material, and a thermally stable manganese-nickel dioxide-type material.

[0013] In yet another exemplary embodiment, a method for making a thermally stable nickel-rich cathode includes providing an active material including a plurality of active material particles. The plurality of active material particles contain nickel. A nanoparticle slurry additive having a plurality of nanoparticles is provided. The plurality of nanoparticles include one or more of a thermally stable olivine-type material, a thermally stable spinel-type material, and a thermally stable manganese-nickel dioxide-type material. The method includes forming a slurry by mixing the active material and the nanoparticle slurry additive. The plurality of nanoparticles form a thermal inhibition layer on the surface of the plurality of active material particles and in direct contact therewith. A free-standing electrode film is formed by calendering the slurry, and the free-standing electrode film is laminated to a current collector to define a thermally stable nickel-rich cathode.

[0014] The present invention discloses the following scheme:

[0015] Solution 1. A vehicle comprising:

[0016] Electric motor; and

[0017] a battery pack electrically coupled to the electric motor, the battery pack comprising an electrochemical cell, the electrochemical cell comprising:

[0018] cathode;

[0019] an anode; and

[0020] an electrolyte system between the cathode and the anode;

[0021] wherein the cathode comprises:

[0022] an active material comprising a plurality of active material particles, the plurality of active material particles comprising nickel; and

[0023] A thermal inhibition layer is formed on a surface of each of the plurality of active material particles and is in direct contact therewith, the thermal inhibition layer comprising a plurality of nanoparticles, the plurality of nanoparticles comprising one or more of a thermally stable olivine-type material, a thermally stable spinel-type material, and a thermally stable manganese-nickel dioxide-type material.

[0024] Option 2. The vehicle according to Option 1, wherein the plurality of nanoparticles comprises a combination of two or more of the thermally stable olivine-type material, the thermally stable spinel-type material, and the thermally stable manganese-nickel dioxide-type material.

[0025] Option 3. A vehicle according to Option 1, wherein the thermally stable olivine-type material includes one or more of lithium vanadium phosphate, lithium iron manganese phosphate, cobalt phosphate and lithium titanium phosphate.

[0026] Option 4. The vehicle according to Option 1, wherein the thermally stable spinel-type material comprises one or more of lithium manganese oxide and lithium manganese nickel oxide.

[0027] Option 5. A vehicle according to Option 1, wherein the thermally stable manganese-nickel dioxide type material comprises one or more of lithium manganese dioxide and lithium manganese nickel dioxide.

[0028] Embodiment 6. The vehicle according to embodiment 1, wherein the mass ratio of the plurality of nanoparticles in the cathode to the active material is less than 30%.

[0029] Embodiment 7. The vehicle according to embodiment 1, wherein the surface coverage of the active material by the plurality of nanoparticles is 10% to 95%.

[0030] Embodiment 8. An electrochemical cell comprising:

[0031] cathode;

[0032] an anode; and

[0033] an electrolyte system between the cathode and the anode;

[0034] wherein the cathode comprises:

[0035] an active material comprising a plurality of active material particles, the plurality of active material particles comprising nickel; and

[0036] A thermal inhibition layer is formed on a surface of each of the plurality of active material particles and is in direct contact therewith, the thermal inhibition layer comprising a plurality of nanoparticles, the plurality of nanoparticles comprising one or more of a thermally stable olivine-type material, a thermally stable spinel-type material, and a thermally stable manganese-nickel dioxide-type material.

[0037] Option 9. An electrochemical cell according to Option 8, wherein the plurality of nanoparticles comprises a combination of two or more of the thermally stable olivine-type material, the thermally stable spinel-type material, and the thermally stable manganese-nickel dioxide-type material.

[0038] Option 10. An electrochemical cell according to Option 8, wherein the thermally stable olivine-type material comprises one or more of lithium vanadium phosphate, lithium iron manganese phosphate, cobalt phosphate and lithium titanium phosphate.

[0039] Option 11. An electrochemical cell according to Option 8, wherein the thermally stable spinel material comprises one or more of lithium manganese oxide and lithium manganese nickel oxide.

[0040] Option 12. An electrochemical cell according to Option 8, wherein the thermally stable manganese-nickel dioxide type material comprises one or more of lithium manganese dioxide and lithium manganese nickel dioxide.

[0041] Embodiment 13. The electrochemical cell according to Embodiment 8, wherein the mass ratio of the plurality of nanoparticles in the cathode to the active material is less than 30%.

[0042] Embodiment 14. The electrochemical cell according to Embodiment 8, wherein the surface coverage of the active material by the plurality of nanoparticles is 10% to 95%.

[0043] Scheme 15. A method for manufacturing a thermally stable nickel-rich cathode, the method comprising:

[0044] providing an active material including a plurality of active material particles, the plurality of active material particles comprising nickel;

[0045] providing a nanoparticle slurry additive including a plurality of nanoparticles, the plurality of nanoparticles comprising one or more of a thermally stable olivine-type material, a thermally stable spinel-type material, and a thermally stable manganese-nickel dioxide-type material;

[0046] forming a slurry by mixing the active material and the nanoparticle slurry additive, wherein the plurality of nanoparticles form a thermal inhibition layer on surfaces of and in direct contact with the plurality of active material particles;

[0047] forming a free-standing electrode film by calendaring the slurry; and

[0048] The free-standing electrode film is laminated to a current collector to define a thermally stable nickel-rich cathode.

[0049] Option 16. A method according to Option 15, wherein the plurality of nanoparticles comprises a combination of two or more of the thermally stable olivine-type material, the thermally stable spinel-type material, and the thermally stable manganese-nickel dioxide-type material.

[0050] Option 17. A method according to Option 15, wherein the thermally stable olivine-type material includes one or more of lithium vanadium phosphate, lithium iron manganese phosphate, cobalt phosphate and lithium titanium phosphate.

[0051] Option 18. A method according to Option 15, wherein the thermally stable spinel material includes one or more of lithium manganese oxide and lithium manganese nickel oxide.

[0052] Option 19. A method according to Option 15, wherein the thermally stable manganese-nickel dioxide type material includes one or more of lithium manganese dioxide and lithium manganese nickel dioxide.

[0053] Option 20. A method according to Option 15, wherein the mass ratio of the plurality of nanoparticles to the active material in the thermally stable nickel-rich cathode is less than 20%.

[0054] The above features and advantages and other features and advantages of the present disclosure will be readily apparent from the following detailed description when taken in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Other features, advantages and details appear, by way of example only, in the following detailed description, which refers to the accompanying drawings, in which:

[0056] Figure 1 is a vehicle configured according to one or more embodiments;

[0057] Figure 2A is a simplified configuration of an electrochemical cell of a battery pack according to one or more embodiments;

[0058] Figure 2B According to one or more embodiments, Figure 2A An exemplary material matrix for a cathode of an electrochemical cell;

[0059] Figure 3 is a method workflow for a method of making a slurry of a thermally stable nickel-rich cathode according to one or more embodiments;

[0060] Figure 4is a method workflow for another slurry manufacturing method of a thermally stable nickel-rich cathode according to one or more embodiments;

[0061] Figure 5 is a method workflow for yet another method of making a slurry of a thermally stable nickel-rich cathode according to one or more embodiments; and

[0062] Figure 6 is a flow chart according to one or more embodiments. DETAILED DESCRIPTION

[0063] The following description is merely exemplary in nature and is not intended to limit the present disclosure, its application or use. It should be understood that throughout the drawings, corresponding reference numerals indicate similar or corresponding parts and features. As used herein, the term module refers to a processing circuit, which may include an application specific integrated circuit (ASIC), an electronic circuit, a processor (shared, dedicated or group) and a memory to execute one or more software or firmware programs, a combinational logic circuit, and / or other suitable components that provide the described functionality.

[0064] As mentioned above, modern automotive high voltage battery packs prefer high energy density materials, such as nickel-based cathodes, to improve energy density and charge / discharge efficiency. Unfortunately, nickel-rich cathodes such as NCMA (LiNi x Co y Mn z Al 1-x-y-z O 2 )、NCA(LiNi x Co y Al 1-x-y O 2 ) and NMC811(LiNi x Mn y Co 1-x-y O 2 ) inherently face challenges related to thermal stability. For example, these nickel-rich cathode materials decompose below 300 degrees Celsius to produce O 2 , O 2 Can react adversely with battery components. Additionally, the high energy density of nickel-rich cathodes can lead to increased heat generation during elevated operating temperatures, such as when the battery pack is rapidly charged or discharged at high rates. Thermal stability issues can lead to battery pack degradation and reduced cycle life.

[0065] It is well known that during cathode manufacturing, a heat-stable material such as lithium manganese iron phosphate (LMFP, LiMn x Fe 1-x PO 4, where x is greater than or equal to 0.4) is introduced into the active material to improve the thermal stability of the electrode. However, a trade-off is that the high mass ratio of LMFP in the hybrid electrode can reduce energy density and reduce fast charging capabilities. Therefore, current cathode and cathode manufacturing technologies must find a balance between thermal stability goals and energy density (battery pack performance).

[0066] The present disclosure introduces a manufacturing method for enhancing the thermal stability of nickel-rich cathodes while eliminating or mitigating the energy density tradeoff. Instead of incorporating bulk thermally stable materials (e.g., LMFP) directly into the active material, a nanoparticle slurry is introduced as an additive to construct a thermally inhibiting layer on the surface of the nickel-rich active material particles. The nanoparticle slurry includes a combination of two or three thermally stable material types: an olivine type, such as lithium vanadium phosphate (LiVOPO 4 ), LMFP, cobalt phosphate (CoPO 4 ), lithium titanium phosphate (LiTi 2 (PO 4 ) 3 ), spinel type, such as LMO, LNMO, and manganese-nickel dioxide type, such as lithium manganese dioxide (LiMnNiO 2 ) and lithium manganese nickel dioxide (LiMn 0.7 Ni 0.3 O 2 ). The thermally stable material may be mixed with a solvent and / or may include a binder and a slurry stabilizer, such as methylcellulose. The resulting nanoscale thermal inhibition layer protects the underlying active material from thermal effects.

[0067] The thermally stable nickel-rich cathode manufactured according to one or more embodiments provides a variety of technical advantages over other nickel-rich cathodes. It is worth noting that the nickel-rich cathode constructed from a slurry of nano-sized particle additives can reduce the mixing ratio without sacrificing the thermal and electrochemical properties of the mixed electrode. In other words, the mass ratio of the thermally stable nanoparticle additive can be reduced without losing thermal stability and battery performance compared to other methods. In some embodiments, the mass ratio of nanoparticles in the final electrode is only 1% to 30%, such as 3% to 5% (or 5% to 20%, or 7% to 15%). For example, in some embodiments, the mass ratio of nanoparticles in the final electrode is less than 20%. In some embodiments, the mass ratio of nanoparticles in the final electrode is less than 10%. In some embodiments, the mass ratio of nanoparticles in the final electrode is less than 5%. Other advantages are also possible. Specifically, a pre-formulated nano-additive slurry with a solid content of about 25% to about 45% can be easily integrated directly into the active material slurry at existing factory facilities, followed by intensive mixing, coating and pressing without significant overhaul of existing equipment.

[0068] According to an exemplary embodiment, a vehicle Figure 1 100. The vehicle 100 is shown in the form of an automobile having a body 102. The body 102 includes a passenger compartment 104, within which a steering wheel, front seats, and rear passenger seats (not shown separately) are arranged. A plurality of components are arranged within the body 102, including, for example, an electric motor 106 (shown by a projection under the front hood). The electric motor 106 is shown for ease of illustration and discussion only. It should be understood that the configuration, location, size, arrangement, etc. of the electric motor 106 are not meant to be particularly limited, and all such configurations (including multi-motor configurations) are within the intended scope of the present disclosure.

[0069] The electric motor 106 is powered via a battery pack 108 (shown by a projection near the rear of the vehicle 100). The battery pack 108 is shown for ease of illustration and discussion only. It should be understood that the configuration, location, size, arrangement, etc. of the battery pack 108 are not meant to be particularly limited, and all such configurations (including split configurations) are within the intended scope of the present disclosure. In addition, while the present disclosure is primarily discussed in the context of a battery pack 108 configured as an electric motor 106 for the vehicle 100, the aspects described herein may be similarly incorporated into any system (vehicle, building, or other) having (one or more) energy storage systems (e.g., one or more battery packs or modules), and all such configurations and applications are within the intended scope of the present disclosure.

[0070] As previously mentioned, in some embodiments, the battery pack 108 includes a thermally stable nickel-rich cathode (refer to Figure 2A ). refer to Figure 2B Exemplary material matrices for thermally stable nickel-rich cathodes are discussed in more detail. Figure 3 , 4 and 5 discuss in more detail exemplary methods for making thermally stable nickel-rich cathodes.

[0071] Figure 2A A battery pack (eg, Figure 1 A simplified configuration of an electrochemical cell of a battery pack 108). Figure 2A As shown in FIG. 1 , an electrochemical cell 200 may include a cathode 202 (i.e., a positive electrode), an anode 204 (i.e., a negative electrode), and an electrolyte system 206 between the cathode 202 and the anode 204. Although only a single electrochemical cell 200 is shown for convenience, it should be understood that the battery pack may contain any number of cells as needed to meet battery pack design constraints (e.g., capacity requirements).

[0072] In some embodiments, cathode 202 is a thermally stable nickel-rich cathode having an active material coated with thermally stable nanoparticles. Figure 2BAn exemplary material matrix for cathode 202 is discussed in more detail.

[0073] In some embodiments, the active material (also referred to as an electroactive material) of the cathode 202 may include a lithium-based active material that can fully perform lithium insertion and extraction, alloying and dealloying, and / or plating and stripping while serving as the positive terminal of the electrochemical cell 200. The cathode 202 electroactive material may include one or more transition metals, such as manganese (Mn), nickel (Ni), cobalt (Co), chromium (Cr), iron (Fe), vanadium (V), and combinations thereof. In some embodiments, the cathode 202 includes one or both of a lithium transition metal oxide having a layered structure and a lithium transition metal oxide having a spinel phase. For example, in some cases, the cathode 202 may include a spinel-type transition metal oxide, such as lithium manganese oxide (Li 1+x Mn 2-x O 4 ), where x is usually less than 0.15, including LiMn 2 O 4 (LMO) and lithium manganese nickel oxide LiMn 1.5 Ni 0.5 O 4 In some embodiments, cathode 202 may include a layered material such as lithium cobalt oxide (LCO, LiCoO 2 ), lithium nickel oxide (LiNiO 2 ), lithium nickel manganese cobalt oxide (LiNi x Mn y Co z O 2 ), including LiMn 0.33 Ni 0.33 Co 0.33 O 2 , lithium nickel cobalt metal oxide (LiNi 1-x-y Co x M y O 2 ), where "M" may include Al, Mn, etc., such as lithium nickel cobalt aluminum oxide (NCA, LiNiCoAlO 2 ), lithium nickel cobalt manganese oxide (NMC, LiNiCoMnO 2 ) and lithium nickel cobalt manganese aluminum oxide (NCMA, LiNi x Co y Mn z Al 1-x-y-z O 2 Other known lithium transition metal compounds may also be used, such as lithium iron phosphate (LFP, LiFePO 4 ) or lithium iron phosphate (Li 2 FePO 4F). In some embodiments, cathode 202 may include an electroactive material including manganese, such as lithium manganese oxide (Li 1+x Mn 2-x O 4 ), mixed lithium manganese nickel oxide (LiMn 2-x Ni x O 4 ), and / or lithium manganese nickel cobalt oxide (e.g. LiMn / 3Ni / 3Co / 3O 2 ). In lithium-sulfur batteries, cathode 202 may include elemental sulfur as the active material and / or a sulfur-containing active material.

[0074] In some embodiments, the electrolyte system 206 acts as a separator to provide a physical barrier between the cathode 202 and the anode 204. In some embodiments, the electrolyte system 206 includes a dendrite barrier, one or more interface layers, and / or one or more electrolyte layers (not shown separately). In some embodiments, in addition to providing a physical barrier between the cathode 202 and the anode 204, the electrolyte system 206 can also provide a path of least resistance for the internal passage of lithium ions (and related anions) during lithium ion cycling to facilitate the function of the electrochemical cell 200.

[0075] In some embodiments, the anode 204 includes an electroactive material, such as a lithium host material capable of serving as a negative terminal of the electrochemical cell 200. In various aspects, the electroactive material comprises lithium and may be lithium metal. In some embodiments, the anode 204 may include an electroactive lithium host material, such as graphite. In some embodiments, the anode 204 may include a conductive material and one or more polymer binder materials to structurally hold the graphite material together. The negative electrode may include greater than or equal to about 50% to less than or equal to about 100% of the electroactive material (e.g., graphite or a mixture of graphite and lithiated silicon oxide), optionally less than or equal to about 30% of the conductive material and the remainder of the binder. For example, in one embodiment, anode 204 can include an active material including graphite particles doped with a binder material selected from the group consisting of polyvinylidene fluoride (PVdF), ethylene propylene diene rubber (EPDM), and / or carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), compounds and / or mixtures of CMC and SBR, nitrile rubber (NBR), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), sodium alginate, lithium alginate, and combinations thereof, as non-limiting examples. Suitable additional conductive materials can include carbon-based materials and / or conductive polymers. As non-limiting examples, carbon-based materials can include conductive carbon black, conductive acetylene black, acetylene black, carbon black, graphite, graphene, graphene oxide, carbon nanofibers, carbon nanotubes, etc. Examples of conductive polymers include polyaniline, polythiophene, polyacetylene, polypyrrole, etc. In some aspects, a mixture of these conductive materials can be used.

[0076] Figure 2B According to one or more embodiments, Figure 2A An exemplary material matrix 250 of the cathode 202 is shown. Figure 2B , the material matrix 250 may include an active material 252 and a plurality of nanoparticles 254. The active material 252 may be made from a range of suitable electroactive materials, as previously discussed with respect to the cathode 202. For example, in some embodiments, the active material 252 includes NCMA, but other active materials are also within the contemplated scope of the present disclosure.

[0077] like Figure 2B As further shown in FIG. 2 , in some embodiments, a plurality of nanoparticles 254 are bound to the surface of the active material 252. In some embodiments, the nanoparticles 254 are fixed to the surface of the active material 252 by introducing a nanoparticle slurry into a wet or dry active material solution. In some embodiments, the nanoparticles 254 are uniformly and / or randomly (as shown) distributed on the surface of the active material 252. Figure 3 , 4and 5 discuss in more detail an exemplary fabrication method utilizing nanoparticle slurries to produce thermally stable nickel-rich cathodes.

[0078] In some embodiments, the nanoparticles 254 are thermally stable nanoparticles, and the plurality of nanoparticles 254 together generally define a thermally inhibiting layer of the active material 252. In some embodiments, the nanoparticles 254 include a thermally stable material type, such as an olivine type, such as LiVOPO 4 ,LMFP,LFP,CoPO 4 、LiTi 2 (PO 4 ) 3 , spinel type, such as LMO, LNMO, and manganese-nickel dioxide type, such as LiMnNiO 2 、LiMn 0.7 Ni 0.3 O 2 In some embodiments, nanoparticles 254 include a combination of two or three thermally stable material types.

[0079] In some embodiments, the surface coverage of active material 252 is about 15% to about 95%, such as 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90% and 95%. In some embodiments, the mass ratio of nanoparticles 254 in the final electrode (e.g., in cathode 202) is only 1% to 30%, such as 3% to 5% (or 5% to 20%, or 7% to 15%). For example, in some embodiments, the mass ratio of nanoparticles in the final electrode is less than 20%. In some embodiments, the mass ratio of nanoparticles in the final electrode is less than 10%. In some embodiments, the mass ratio of nanoparticles in the final electrode is less than 5%.

[0080] In some embodiments, the matrix 250 includes a solvent, a binder, and / or a slurry stabilizer (not shown separately). The solvent may be selected from known materials according to the selection of the active material 252. For example, the solvent of the NCMA active material may include N-methyl-2-pyrrolidone (NMP). Other solvents are also feasible, such as cyclic carbonates (e.g., ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), fluoroethylene carbonate (FEC)); acyclic (i.e., linear) carbonates (e.g., dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC)); aliphatic carboxylates (e.g., methyl formate, methyl acetate, methyl propionate); γ-lactones (e.g., γ-butyrolactone, γ-valerolactone); chain structure ethers (e.g., 1,2-dimethoxyethane, 1-2-diethoxyethane, ethoxymethoxyethane); cyclic ethers (e.g., tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane); and combinations thereof.

[0081] Binder can be selected from a series of suitable materials, such as polyvinylidene fluoride polymer (PVDF). Other binder materials are feasible, such as polytetrafluoroethylene (PTFE), ethylene propylene diene monomer rubber (EPDM), carboxymethyl cellulose (CMC), nitrile rubber (NBR), styrene-ethylene-butylene-styrene copolymer (SEBS), styrene-butylene-styrene copolymer (SBS), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), sodium alginate and lithium alginate. In some embodiments, binder is incorporated in a weight ratio of 1% to 10% (e.g., 3%), but other weight ratios are also within the expected range of the present disclosure.

[0082] The slurry stabilizer may include materials such as methylcellulose. In some embodiments, the stabilizer is incorporated at a weight ratio of 0.05% to 5%, such as 0.5%, although other weight ratios are also within the contemplated scope of the present disclosure.

[0083] Figure 3 A method workflow 300 of a method for making a slurry of a thermally stable nickel-rich cathode according to one or more embodiments is shown. The workflow 300 can be performed as part of forming a cathode (e.g., cathode 202) of an electrochemical cell (e.g., electrochemical cell 200). It should be understood that while the method workflow 300 is primarily discussed for a single cell for convenience and ease of illustration, the basic techniques can be repeated to produce cathodes for any number of cells in a battery pack.

[0084] Workflow 300 begins at box 302, where active materials, binder materials, and conductive additives are purchased and / or otherwise prepared for mixing. In some embodiments, the active material may include a nickel-rich active material, such as NCMA, NCA, and / or NMC811. In some embodiments, the binder material may include one or more of PVDF, EPDM, CMC, SBR, NBR, LiPAA, NaPAA, sodium alginate, lithium alginate, and combinations thereof. In some embodiments, the binder material includes PVDF. In some embodiments, the conductive additive may include carbon black, acetylene black, enhanced carbon black (also known as SuperP or SP), graphite, graphene, graphene oxide, carbon nanofibers, carbon nanotubes, etc. In some embodiments, the active material, binder material, and conductive additive are purchased as dry powders. In some embodiments, the active material, binder material, and conductive additive are purchased as dry powders with 100% solid content.

[0085] At block 304, the active material, binder material, and conductive additive are subjected to a dry powder mixing process. In some embodiments, the active material, binder material, and conductive additive are dry mixed for 30 minutes using a planetary mixer having a low speed of 10 to 50 revolutions per minute (RPM) (e.g., 20 RPM) and a high speed of 0 to 1000 RPM (e.g., 0 RPM). In some embodiments, dry mixing is performed at a temperature of about 25 degrees Celsius, but other temperatures are also within the contemplated range of the present disclosure.

[0086] At block 306, a solvent is mixed into the dry powder mixture of the active material, binder material, and conductive additive to define an active material slurry. In some embodiments, the solvent includes NMP. In some embodiments, the solvent is added to achieve a solid content in the active material slurry of 100% to 70%, such as a target of 76%.

[0087] At frame 308, the active material slurry is folded, stirred and / or otherwise agitated to ensure uniform wetting of the particles. This process may be referred to as kneading. In some embodiments, mechanical stirring and / or other mixing techniques are used to continuously mix and knead the active material slurry to obtain a consistent and well-dispersed slurry. Kneading ensures that the active material particles are uniformly coated with solvent to form a pasty consistency. In some embodiments, mixing and kneading (frames 304 and 306) occur substantially simultaneously, wherein the solvent is slowly and incrementally added to the base dry powder until the solid is completely wetted, thereby providing a uniform paste or "slurry". In some embodiments, a planetary mixer with a low speed (e.g., 40RPM) of 1 to 100RPM and a high speed (e.g., 500RPM) of 100 to 1000RPM is used to knead for 40 minutes. In some embodiments, kneading is carried out at a temperature of about 25 degrees Celsius, but other temperatures are also within the expected range of the present disclosure. In some embodiments, kneading is continued until the solid content is about 76%.

[0088] At block 310, a nanoparticle slurry additive is purchased and / or otherwise prepared for mixing with the active material paste / slurry. In some embodiments, the nanoparticle slurry additive includes a plurality of nanoparticles. In some embodiments, the nanoparticles include a thermally stable material type, such as an olivine type, such as LiVOPO 4 ,LMFP,CoPO 4 、LiTi 2 (PO 4 ) 3 , spinel type, such as LMO, LNMO and manganese-nickel dioxide type, such as LiMnNiO 2 、LiMn 0.7 Ni 0.3 O 2 In some embodiments, the nanoparticles include a combination of two or three types of thermally stable materials. In some embodiments, the nanoparticle slurry additive itself is a mixed combination of dry powder nanoparticles and a solvent such as NMP to ensure fluidity. In some embodiments, the mass ratio of nanoparticles in the nanoparticle slurry additive is about 20% to about 50%, such as 25% to 40%. In some embodiments, the viscosity of the nanoparticle slurry additive is less than 8000 millipascals seconds (mPa-s).

[0089] In some embodiments, the nanoparticle slurry additive includes 35 wt % LMFP nanoparticles, 3 wt % methoxycellulose (MC), and 62 wt % NMP.

[0090] At box 312, the nanoparticle slurry additive from box 310 is mixed with the active material paste / slurry from box 308 to define a coated active material slurry (also referred to as a nano-encapsulated active material particle slurry). In some embodiments, a planetary mixer with a low speed of 10 to 100 revolutions per minute (RPM) (e.g., 60 RPM) and a high speed of 1000 to 4000 RPM (e.g., 2000 RPM) is used to mix the nanoparticle slurry additive and the active material paste / slurry. In some embodiments, mixing occurs for one hour. In some embodiments, mixing occurs for 10 minutes, 30 minutes, 1 hour, 2 hours, 4 hours, 8 hours, 12 hours, or 24 hours. In some embodiments, mixing is continued until the solid content is about 72%.

[0091] In some embodiments, as described above, the mass ratio of nanoparticles in the resulting coated active material slurry is only 1% to 30%. For example, the mass ratio of nanoparticles in the coated active material slurry can be 3% to 5%, 5% to 20%, 7% to 15%, etc. In some embodiments, the mass ratio of nanoparticles in the coated active material slurry is less than 20%. In some embodiments, the mass ratio of nanoparticles in the coated active material slurry is less than 10%. In some embodiments, the mass ratio of nanoparticles in the coated active material slurry is less than 5%.

[0092] Optionally, at block 314, additional solvent is mixed into the coated active material slurry from block 312 to further fine tune the solids content. In some embodiments, the additional solvent includes NMP. In some embodiments, the additional solvent is added to bring the solids content to a target of about 30% to 75%, for example 69%.

[0093] At box 316, the optional additional solvent from box 314 is added to the coated active material slurry from box 312 to define a final slurry. In some embodiments, the final slurry can be formed using a planetary mixer with a low speed of 10 to 50 revolutions per minute (RPM) (e.g., 40 RPM) and a high speed of between 1000 and 4000 RPM (e.g., 3000 RPM). In some embodiments, mixing is performed for 40 minutes. In some embodiments, mixing is performed for 10 minutes, 30 minutes, 1 hour, 2 hours, 4 hours, 8 hours, 12 hours, or 24 hours.

[0094] At block 318, the final slurry from block 316 undergoes coating and / or calendaring to form a free-standing electrode film. In some embodiments, the final slurry is pressed in a calendaring machine and the resulting free-standing electrode film is laminated to a current collector to define a nickel-rich cathode with enhanced thermal stability.

[0095] Figure 4A method workflow 400 of another slurry manufacturing method for a thermally stable nickel-rich cathode according to one or more embodiments is shown. The workflow 400 can be performed as part of forming a cathode (e.g., cathode 202) of an electrochemical cell (e.g., electrochemical cell 200). It should be understood that while the method workflow 400 is primarily discussed for a single cell for convenience and ease of illustration, the basic techniques can be repeated to produce cathodes for any number of cells in a battery pack.

[0096] Workflow 400 begins at frame 402, where binder materials and solvents are purchased and / or otherwise prepared for mixing. In some embodiments, the binder material may include one or more of PVDF, EPDM, CMC, NBR, LiPAA, NaPAA, sodium alginate, lithium alginate, and combinations thereof. In some embodiments, the binder material includes PVDF. In some embodiments, the solvent includes NMP.

[0097] In some embodiments, binder material and solvent are premixed at a temperature of 25 to 55 degrees Celsius. In some embodiments, a planetary mixer with a low speed (e.g., 20RPM) of 10 to 100RPM and a high speed (e.g., 400RPM) of 100 to 1000RPM is used to mix binder material and solvent. In some embodiments, mixing is carried out for 100 minutes. In some embodiments, mixing is carried out for 10 minutes, 30 minutes, 1 hour, 2 hours, 4 hours, 8 hours, 12 hours, or 24 hours. In some embodiments, the binder material and solvent mixed include a solid content of 5% to 15%, for example, 8%.

[0098] At block 404, the binder material and the solvent are mixed to define a solution. In some embodiments, the solvent is added to the solution to completely wet the binder material, which may be purchased as a dry powder.

[0099] At frame 406, conductive additives are added to the solution from frame 404. In some embodiments, conductive additives may include carbon black, acetylene black, enhanced carbon black (also known as Super P or SP), graphite, graphene, graphene oxide, carbon nanofibers, carbon nanotubes, etc. In some embodiments, conductive additives are incorporated at a temperature of 25 degrees Celsius. In some embodiments, a planetary mixer with a low speed (e.g., 40RPM) of 10 to 100RPM and a high speed (e.g., 2000RPM) of 1000 to 4000RPM is used to incorporate conductive additives. In some embodiments, mixing is performed for 30 minutes. In some embodiments, mixing is performed for 10 minutes, 30 minutes, 1 hour, 2 hours, 4 hours, 8 hours, 12 hours, or 24 hours. In some embodiments, the solid content after adding the conductive additive is 7% to 20%, for example, 12%.

[0100] At block 408, the solution and the conductive additive are mixed to define a first slurry. In some embodiments, a planetary mixer having a low speed of 10 to 50 revolutions per minute (RPM) (e.g., 40 RPM) and a high speed of 1000 to 4000 RPM (e.g., 2000 RPM) is used to mix the solution and the conductive additive.

[0101] At block 410, a nanoparticle slurry additive is purchased and / or otherwise prepared for mixing with the first slurry from block 408. In some embodiments, the nanoparticle slurry additive includes a plurality of nanoparticles. In some embodiments, the nanoparticles include a thermally stable material type, such as an olivine type, such as LiVOPO 4 ,LMFP,CoPO 4 、LiTi 2 (PO 4 ) 3 , spinel type, such as LMO, LNMO, and manganese-nickel dioxide type, such as LiMnNiO 2 、LiMn 0.7 Ni 0.3 O 2 In some embodiments, the nanoparticles include a combination of two or three thermally stable material types. In some embodiments, the nanoparticle slurry additive itself is a mixed combination of dry powder nanoparticles and a solvent, such as NMP, to ensure flowability.

[0102] In some embodiments, the nanoparticle slurry additive includes 35 wt % LMFP nanoparticles, 3 wt % methoxycellulose (MC), and 62 wt % NMP.

[0103] In some embodiments, the mass ratio of nanoparticles in the nanoparticle slurry additive is about 20% to about 50%, such as 35% to 45%. In some embodiments, the viscosity of the nanoparticle slurry additive is less than 8000 millipascal-seconds (mPa-s).

[0104] At frame 412, the nanoparticle slurry additive is mixed with the first slurry to define a second slurry. In some embodiments, a planetary mixer with a low speed (e.g., 40 RPM) of 10 to 50 RPM and a high speed (e.g., 2000 RPM) of 1000 to 4000 RPM can be used to form the second slurry. In some embodiments, mixing is performed for 30 minutes. In some embodiments, mixing is performed for 10 minutes, 30 minutes, 1 hour, 2 hours, 4 hours, 8 hours, 12 hours, or 24 hours. In some embodiments, mixing is performed at a temperature of 25 degrees Celsius.

[0105] At block 414, active material is added to the second slurry from block 412. In some embodiments, the active material may include a nickel-rich active material, such as NCMA, NCA, and / or NMC811.

[0106] Optionally, at block 416, additional solvent is added to the second slurry to further fine tune the solids content. In some embodiments, the additional solvent includes NMP. In some embodiments, the additional solvent is added to achieve a target solids content of about 50% to 80%, such as 72%.

[0107] At frame 418, the active material from frame 414, the optional additional solvent from frame 416, and the second slurry from frame 412 are mixed to define a third slurry. In some embodiments, a planetary mixer with a low speed of 10 to 50 revolutions per minute (RPM) (e.g., 40 RPM) and a high speed of 1000 to 4000 RPM (e.g., 3000 RPM) can be used to form the third slurry. In some embodiments, mixing is performed for 100 minutes. In some embodiments, mixing is performed for 10 minutes, 30 minutes, 1 hour, 2 hours, 4 hours, 8 hours, 12 hours, or 24 hours. In some embodiments, the resulting mixture comprises a solid content of 50% to 80%, for example, 69%. In some embodiments, mixing is performed at a temperature of 25 degrees Celsius.

[0108] At block 420, the third slurry from block 418 undergoes coating and / or calendaring to form a free-standing electrode film. In some embodiments, the third slurry is pressed in a calendaring machine and the resulting free-standing electrode film is laminated to a current collector to define a nickel-rich cathode with enhanced thermal stability.

[0109] Figure 5A method workflow 500 of yet another slurry manufacturing method for a thermally stable nickel-rich cathode according to one or more embodiments is shown. The workflow 500 can be performed as part of forming a cathode (e.g., cathode 202) of an electrochemical cell (e.g., electrochemical cell 200). It should be understood that while the method workflow 500 is primarily discussed for a single cell for convenience and ease of illustration, the basic techniques can be repeated to produce cathodes for any number of cells in a battery pack.

[0110] Workflow 500 begins at box 502, where a slurry stabilizer and solvent are purchased and / or otherwise prepared for mixing. In some embodiments, the slurry stabilizer may include methylcellulose, but other stabilizers are also within the contemplated scope of the present disclosure. In some embodiments, the solvent includes NMP.

[0111] At block 504, a slurry stabilizer and a solvent are mixed to define a solution. In some embodiments, the slurry stabilizer and the solvent are mixed with an active material. In some embodiments, the active material may include a nickel-rich active material, such as NCMA, NCA, and / or NMC811.

[0112] In some embodiments, solvent is added to the solution to completely wet the slurry stabilizer and / or active material. In some embodiments, a planetary mixer with a low speed of 10 to 50 revolutions per minute (RPM) (e.g., 20 RPM) and a high speed of 1000 to 4000 RPM (e.g., 2000 RPM) is used to mix the slurry stabilizer, solvent, and active material. In some embodiments, mixing is performed for one hour. In some embodiments, the solid content of the solution is 8% to 12%.

[0113] At block 506, a nanoparticle slurry additive is purchased and / or otherwise prepared for mixing with the solution from block 504. In some embodiments, the nanoparticle slurry additive includes a plurality of nanoparticles. In some embodiments, the nanoparticles include a thermally stable material type, such as an olivine type, such as LiVOPO 4 ,LMFP,CoPO 4 、LiTi 2 (PO 4 ) 3 , spinel type, such as LMO, LNMO, and manganese-nickel dioxide type, such as LiMnNiO 2 、LiMn 0.7 Ni 0.3 O 2 In some embodiments, the nanoparticles include a combination of two or three thermally stable material types. In some embodiments, the nanoparticle slurry additive itself is a mixed combination of dry powder nanoparticles and a solvent, such as NMP, to ensure flowability.

[0114] At box 508, the nanoparticle slurry additive (with or without solvent) from box 506 and the solution from box 504 are mixed to define a first slurry. In some embodiments, a planetary mixer with a low speed of 10 to 50 revolutions per minute (RPM) (e.g., 30 RPM) and a high speed of 1000 to 4000 RPM (e.g., 2000 RPM) is used to mix the first slurry. In some embodiments, mixing is performed for one hour. In some embodiments, the solid content of the first slurry is 45% to 55%, for example, 50%.

[0115] In some embodiments, the nanoparticle slurry additive in the first slurry coats the active material. In some embodiments, the nanoparticle slurry additive is LMFP and the first slurry includes an active material (eg, NCMA) encapsulated (coated) with LMFP.

[0116] At frame 510, a solvent is mixed into the first slurry from frame 508 to define a second slurry at frame 512. In some embodiments, the solvent includes NMP. In some embodiments, the solvent is added to reach a solid content of 30% to 50%, such as 40%, in the second slurry. In some embodiments, a planetary mixer with a low speed of 10 to 50 revolutions per minute (RPM) (e.g., 30 RPM) and a high speed of 1000 to 4000 RPM (e.g., 3000 RPM) is used to mix the second slurry. In some embodiments, mixing is performed for half an hour.

[0117] At block 514, the second slurry from block 512 is degassed. In some embodiments, the degassing is performed in a vacuum. In some embodiments, the degassing is performed for half an hour. In some embodiments, the degassing is performed for at least half an hour, such as 1 hour, 2 hours, 4 hours, etc. In some embodiments, the solid content of the second slurry after degassing is 30% to 50%, for example, 40%.

[0118] At frame 516, a binder, a conductive additive, and / or a processing solvent are mixed with the second slurry from frame 514. In some embodiments, the binder material may include one or more of PVDF, EPDM, CMC, NBR, LiPAA, NaPAA, sodium alginate, lithium alginate, and combinations thereof. In some embodiments, the binder material includes PTFE. In some embodiments, the binder is incorporated in a weight ratio of 1% to 5%, such as 3%, but other weight ratios are also within the expected range of the present disclosure. In some embodiments, the conductive additive may include carbon black, acetylene black, enhanced carbon black (also referred to as SuperP or SP), graphite, graphene, graphene oxide, carbon nanofibers, carbon nanotubes, etc. In some embodiments, the processing solvent may include NMP.

[0119] At box 518, the mixture from box 516 undergoes coating and / or calendaring to form a self-supporting electrode film. In some embodiments, the mixture is pressed in a calendaring machine to define the resulting self-supporting electrode film. At box 520, the self-supporting electrode film from box 518 is laminated to a current collector to define a nickel-rich cathode with enhanced thermal stability.

[0120] Reference now Figure 6 , generally shows a flow chart 600 for making a thermally stable nickel-rich cathode according to one embodiment. Although depicted in a particular order, Figure 6 The blocks shown in may be rearranged, subdivided and / or combined.

[0121] At block 602, the method includes providing an active material including a plurality of active material particles. In some embodiments, the plurality of active material particles include nickel. In some embodiments, the active material may include a nickel-rich active material, such as NCMA, NCA, and / or NMC811.

[0122] At block 604, the method includes providing a nanoparticle slurry additive including a plurality of nanoparticles. In some embodiments, the plurality of nanoparticles includes one or more of a thermally stable olivine-type material, a thermally stable spinel-type material, and a thermally stable manganese-nickel dioxide-type material.

[0123] In some embodiments, the plurality of nanoparticles includes a combination of two or more of a thermally stable olivine-type material, a thermally stable spinel-type material, and a thermally stable manganese-nickel dioxide-type material.

[0124] In some embodiments, the thermally stable olivine-type material includes one or more of lithium vanadium phosphate, lithium iron manganese phosphate, cobalt phosphate, and lithium titanium phosphate. In some embodiments, the thermally stable spinel-type material includes one or more of lithium manganese oxide and lithium manganese nickel oxide. In some embodiments, the thermally stable manganese-nickel dioxide-type material includes one or more of lithium manganese dioxide and lithium manganese dioxide nickel.

[0125] At block 606, the method includes forming a slurry by mixing the active material and the nanoparticle slurry additive. In some embodiments, the plurality of nanoparticles forms a thermal inhibition layer on a surface of and in direct contact with the plurality of active material particles.

[0126] At block 608 , the method includes forming a free-standing electrode film by hot rolling / calendering the slurry and / or dry powder mixture.

[0127] At block 610 , the method includes laminating a free-standing electrode film to a current collector to define a thermally stable nickel-rich cathode.

[0128] In some embodiments, the mass ratio of the plurality of nanoparticles to the active material in the cathode is less than 20%. In some embodiments, the surface coverage of the plurality of nanoparticles to the active material comprises 15% to 95%.

[0129] The terms "a" and "an" do not indicate a quantitative limitation, but rather indicate the presence of at least one of the referenced items. The term "or" means "and / or" unless the context clearly indicates otherwise. References to "an aspect" throughout the specification mean that a particular element (e.g., feature, structure, step, or characteristic) described in conjunction with that aspect is included in at least one aspect described herein, and may or may not be present in other aspects. In addition, it should be understood that the described elements may be combined in any suitable manner in the various aspects.

[0130] When an element such as a layer, film, region, or substrate is referred to as being "on" another element, it can be directly on the other element or intervening elements may also be present. In contrast, when an element is referred to as being "directly on" another element, there are no intervening elements present.

[0131] Unless otherwise specified herein, all test standards are the most current standards in effect as of the filing date of this application or, if priority is claimed, the filing date of the earliest priority application in which such test standard appears.

[0132] Unless defined otherwise, technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure belongs.

[0133] Although the above disclosure has been described with reference to exemplary embodiments, it will be appreciated by those skilled in the art that various changes may be made and elements thereof may be substituted with equivalents without departing from its scope. In addition, many modifications may be made to adapt specific circumstances or materials to the teachings of the present disclosure without departing from its essential scope. Therefore, the present disclosure is not intended to be limited to the specific embodiments disclosed, but will include all embodiments falling within its scope.

Claims

1. A vehicle comprising: Electric motor; and a battery pack electrically coupled to the electric motor, the battery pack comprising an electrochemical cell, the electrochemical cell comprising: cathode; an anode; and an electrolyte system between the cathode and the anode; wherein the cathode comprises: an active material comprising a plurality of active material particles, the plurality of active material particles comprising nickel; and A thermal inhibition layer is formed on a surface of each of the plurality of active material particles and is in direct contact therewith, the thermal inhibition layer comprising a plurality of nanoparticles, the plurality of nanoparticles comprising one or more of a thermally stable olivine-type material, a thermally stable spinel-type material, and a thermally stable manganese-nickel dioxide-type material. 2 . The vehicle of claim 1 , wherein the plurality of nanoparticles comprises a combination of two or more of the thermally stable olivine-type material, the thermally stable spinel-type material, and the thermally stable manganese-nickel dioxide-type material. 3 . The vehicle of claim 1 , wherein the thermally stable olivine-type material comprises one or more of lithium vanadium phosphate, lithium iron manganese phosphate, cobalt phosphate, and lithium titanium phosphate. 4 . The vehicle of claim 1 , wherein the thermally stable spinel-type material comprises one or more of lithium manganese oxide and lithium manganese nickel oxide. 5 . The vehicle of claim 1 , wherein the thermally stable manganese-nickel dioxide type material comprises one or more of lithium manganese dioxide and lithium manganese nickel dioxide. 6 . The vehicle of claim 1 , wherein a mass ratio of the plurality of nanoparticles to the active material in the cathode is less than 30%. 7 . The vehicle of claim 1 , wherein the surface coverage of the active material by the plurality of nanoparticles is 10% to 95%.

8. An electrochemical cell comprising: cathode; anode; and an electrolyte system between the cathode and the anode; wherein the cathode comprises: an active material comprising a plurality of active material particles, the plurality of active material particles comprising nickel; and A thermal inhibition layer is formed on a surface of each of the plurality of active material particles and is in direct contact therewith, the thermal inhibition layer comprising a plurality of nanoparticles, the plurality of nanoparticles comprising one or more of a thermally stable olivine-type material, a thermally stable spinel-type material, and a thermally stable manganese-nickel dioxide-type material.

9. The electrochemical cell of claim 8, wherein the plurality of nanoparticles comprises a combination of two or more of the thermally stable olivine-type material, the thermally stable spinel-type material, and the thermally stable manganese-nickel dioxide-type material.

10. The electrochemical cell of claim 8, wherein the thermally stable olivine-type material comprises one or more of lithium vanadium phosphate, lithium iron manganese phosphate, cobalt phosphate, and lithium titanium phosphate.